Prevalence of musculoskeletal disorders among members of the Peruvian Society of Endodontics - Gonzales De La Riva, Milena Ekaterine (2025)
Objective: To identify the prevalence of musculoskeletal disorders (MSDs) among members of the Peruvian Society of Endodontics. Materials and methods: The Kuorinka Nordic Musculoskeletal Questionnaire was distributed to members of the society and administered online via Google Forms. Of the responses received, 135 that met the inclusion criteria were analyzed. Results: 66.67% of respondents reported the neck as the area most affected by musculoskeletal disorders (MSDs), with 62.22% reporting this discomfort in the same area during the past week. In contrast, the elbow and forearm showed the least involvement, with a prevalence of 14.07% in the overall analysis, which decreased to 13.33% in the last 12 months and to 6.67% during the past week. Binary logistic regression analysis showed that gender was a significant predictor of MSDs in the neck (OR = 6.01; p < 0.001) and shoulder (OR = 2.99; p = 0.004), with a higher probability in women. In the wrist and hand, age was significant (OR = 0.26; p = 0.033), indicating a lower risk with increasing age. No statistically significant associations were observed in the elbow/forearm and thoracic/lumbar segments. Conclusions: The neck area was the most affected by musculoskeletal disorders (MSDs), followed by the thoracic or lumbar region, the shoulders, and the wrists or hands, in that order. However, this severity decreased in all areas during the last seven days. Furthermore, the elbow and forearm were the least affected areas due to their lower exposure to overload or repetitive movements.